4D synchrotron X-ray tomographic quantification of the transition from cellular to dendrite growth during directional solidification. (15th September 2016) - Cai, B.; Wang, J.; Kao, A.; Pericleous, K.; Phillion, A.B.; Atwood, R.C.; Lee, P.D.
Abstract: Solidification morphology directly impacts the mechanical properties of materials; hence many models of the morphological evolution of dendritic structures have been formulated. However, there is a paucity of validation data for directional solidification models, especially the direct observations of metallic alloys, both for cellular and dendritic structures. In this study, we performed 4D synchrotron X-ray tomographic imaging (three spatial directions plus time), to study the transition from cellular to a columnar dendritic morphology and the subsequent growth of columnar dendrite in a temperature gradient stage. The cellular morphology was found to be highly complex, with frequent lateral bridging. Protrusions growing out of the cellular front with the onset of morphological instabilities were captured, together with the subsequent development of these protrusions into established dendrites. Other mechanisms affecting the solidification microstructure, including dendrite fragmentation/pinch-off were also captured and the quantitative results were compared to proposed mechanisms. The results demonstrate that 4D imaging can provide new data to both inform and validate solidification models. Graphical abstract: